2017
DOI: 10.3892/mmr.2017.6471
|View full text |Cite
|
Sign up to set email alerts
|

Synchronized dual pulse gastric electrical stimulation improves gastric emptying and activates enteric glial cells via upregulation of GFAP and S100B with different courses of subdiaphragmatic vagotomy in rats

Abstract: Previous research and clinical practice have indicated that damage to the vagal nerve may seriously affect gastrointestinal physiological movement behavior. The aim of the current study was to observe the change of gastric motility, as well as enteric glial cells (EGCs) in the stomach with different courses of vagal nerve transection in rats prior to and following synchronized dual pulse gastric electrical stimulation. The gastric emptying rates were measured to assess the gastric motility. The glial markers, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…[20][21][22] In addition, another cannula was placed in the duodenum (10 cm below the pylorus for the assessment of gastric emptying. [23][24][25][26] Immediately after the surgery, antibiotics (cefpodoxime, 10 mg/kg) and pain medications (buprenorphine SR, 0.06 mg/kg) were given for a period of 7 days and 3 days, respectively. The animals were monitored twice daily for a period of at least 2 weeks and no experiments were performed before the dogs were completely recovered from the surgical proce-dures.…”
Section: Animal Preparation and Surgical Proceduresmentioning
confidence: 99%
“…[20][21][22] In addition, another cannula was placed in the duodenum (10 cm below the pylorus for the assessment of gastric emptying. [23][24][25][26] Immediately after the surgery, antibiotics (cefpodoxime, 10 mg/kg) and pain medications (buprenorphine SR, 0.06 mg/kg) were given for a period of 7 days and 3 days, respectively. The animals were monitored twice daily for a period of at least 2 weeks and no experiments were performed before the dogs were completely recovered from the surgical proce-dures.…”
Section: Animal Preparation and Surgical Proceduresmentioning
confidence: 99%
“…In the present study, we demonstrated that SGES with a long pulse (300 msec, 4 mA) followed by 5 short pulses (0.3 msec, 100 Hz, 4 mA) markedly upregulated GDNF expression together with p-Akt and PGP9.5, and reduced the number of TUNEL-positive cells. Our previous studies demonstrated that SGES activated EGCs and improved gastric emptying (31,32). This result indicates that SGES restores injured ENS and improves gastric motility.…”
Section: Discussionmentioning
confidence: 99%
“…Our data indicated that Cx43 expression was markedly reduced in the vagotomized groups and that short- or long-term SGES increased Cx43 expression. Our previous study found that SGES improved gastric emptying in vagotomized rats through the activation of enteric glial cells (32). More research is required to determine whether SGES enhances the cross-talk between enteric glial cells via the Cx43 protein and further promotes the release of GDNF.…”
Section: Discussionmentioning
confidence: 99%